Psalm 104: A bodily interpretation of 'Yahweh's history' - Coetzee, Johan H. (Old Testament Essays, 2008)
Psalm 104 is one of the finest pieces of lyric poetry in the Old Testament, expressing the poet's emotions regarding 'Yahweh's history.' According to Israelite belief, creation was Yahweh's first act in history, the first fundamental deed setting the stage for Yahweh's involvement with his people. The praise of Yahweh's works and wonders in the creation is often mentioned in the same breath as his acts in the history of his people. In this paper 'Yahweh's history,' as expressed in Psalm 104, is examined from a bodily perspective. Our involvement in and contemplation of this 'history' can only be via the body. It is shown how God-constructs, animal behaviour, and descriptions of nature, as depictions within 'Yahweh's history,' all refer back to and are metaphorised from human bodily experiences. Human involvement in the 'history of Yahweh' appears to be on the same level as the rest of creation in this psalm. This has important ethical implications on all levels of our involvement in that 'history.'
free